Respostas
respondido por:
0
Resposta:
Regra de sinais:
(+) com (+) = +
(-) com (-) = +
(+) com (-) = -
(-) com (+) = -
(36-x)+x+(28-x)=42
36 - x + x + 28 - x = 42
- x - x + x = 42 - 36 - 28
- 2x + x = 42 - 64
- 1x = - 22 .(-1)
+1x = + 22
x = + 22
S[22]
Explicação passo a passo:
respondido por:
0
Resposta:
x = 22
Explicação passo-a-passo:
(36 - x) + x + (28 - x) = 42
36 - x + x + 28 - x = 42
x = 36 + 28 - 42
x = 64 - 42
x = 22
Perguntas similares
3 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás